Black Racialization and Resistance at an Elite University - hampton, rosalind (University of Toronto Press, 2023)
The presence and experiences of Black people at elite universities have been largely underrepresented and erased from institutional histories. This book engages with a collection of these experiences that span half a century and reflect differences in class, gender, and national identifications among Black scholars. By mapping Black people's experiences of studying and teaching at McGill University, this book reveals how the "whiteness" of the university both includes and exceeds the racial identities of students and professors. It highlights the specific functions of Blackness and of anti-Blackness within society in general and within the institution of higher education in particular, demonstrating how structures and practices of the university reproduce interlocking systems of oppression that uphold racial capitalism, reproduce colonial relations, and promote settler nationalism. Critically engaging the work of Black learners, academics, organizers, and activists within this dynamic political context, this book underscores the importance of Black Studies across North America.